Penerapan Evaluasi Pembelajaran Berbasis HOTS - Mariam, Popon; Nurhayati, Yeti; Irmawan, Irmawan (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2020)
In the Regulation of the Minister of Education and Culture of the Republic of Indonesia No. 20 Regarding Competency Standards for Primary and Secondary Education Graduates, there is a skill dimension where one of the objectives is that students are expected to have critical thinking and acting skills with scientific skills. In implementing the Permendikbud, the government is fixing HOTS-based educational evaluation standards in every activity, both semester exams and national level exams for SMA and SMK equivalent. HOTS is high-level thinking by carrying out measurement tasks through steps of analyzing, evaluating and creating conceptual and procedural knowledge or metacognitive. Facts in the field based on the analysis show that students are still weak in higher order thinking skills (HOTS) and teachers have difficulty in designing and implementing HOTS-based evaluations. The purpose of this Community Service is to provide training in the preparation of HOTS-based evaluation tools in the learning process. The training and mentoring method is carried out with the in-service training pattern which is carried out in classical presentation, as well as the on-the-job learning pattern or independent mentoring at the training participants' assignments as the implementation of training held at SMKS Putra Padjdjaran 2, Bandung City. The output targets have been achieved, namely (1) an article entitled Making and Implementing HOTS-based Evaluation in Learning submitted to the Tri Bhakti Journal of Langlangbuana University,(2) photo documentation of the implementation, (3) draft teaching materials/modules entitled HOTS-based evaluation, (4) ) the increasing knowledge and ability of teachers of SMKS Putra Padjadjaran 2 Bandung in making and implementing HOTS-based evaluation tools in learning as an effort to improve the quality of the process and learning outcomes. Key Word Learning Evaluation; HOTS